Evaluation of surgical instrument and medical device decontamination and sterilisation practice in Healthcare Facilities - Hakizimana, Boniface (International Journal of Infection Control, 2015)
Effective cleaning and disinfection/sterilisation using a properly validated washer-disinfector/steriliser will protect patients and staff from infection; prolong the life of the equipment and ensure the quality of the diagnostic/therapeutic procedure. The purpose of this study was to evaluate how instrument trays were received in the decontamination area, checked, sorted, cleaned, inspected, wrapped, sterilized and how each processing stage was validated. An audit of the CSSD facility was also conducted. This study was conducted at Tygerberg Hospital during the period of 18th of June to 18th of July 2013 as part of the Intermediate course in decontamination and sterilisation for Postgraduate diploma in Infection prevention and control. This was a descriptive survey, whereby an audit tool and other observational tools for capturing the required information were developed and used to collect information. The results from the audit conducted at CSSD from 21st June to 5th July 2013 indicated 86% compliance. The control of instruments before and after use was not documented in 37% and 60% cases respectively. There was lack of displayed written SOPs for reusable instruments onwards, and for instruments manual cleaning in CSSD. A good program of decontamination and sterilization was observed in the CSSD of TBH. However, some improvements are still needed such as proper use of detergents, hand hygiene practice, use of PPE, record keeping. Staff training, developing and displaying of required SOPs, regular monitoring and evaluation of activities should also be tackled to enhance the compliance.